Apoplastic Peroxidases and Lignification in Needles of Norway Spruce (Picea abies L.). - Polle, A. (1994)
The objective of the present study was to investigate the correlation of soluble apoplastic peroxidase activity with lignification in needles of field-grown Norway spruce (Picea abies L.) trees. Apoplastic peroxidases (EC 1.11.1.7) were obtained by vacuum infiltration of needles. The lignin content of isolated cell walls was determined by the acetyl bromide method. Accumulation of lignin and seasonal variations of apoplastic peroxidase activities were studied in the first year of needle development. The major phase of lignification started after bud break and was terminated about 4 weeks later. This phase correlated with a transient increase in apoplastic guaiacol and coniferyl alcohol peroxidase activity. NADH oxidase activity, which is thought to sustain peroxidase activity by production of H2O2, peaked sharply after bud break and decreased during the lignification period. Histochemical localization of peroxidase with guaiacol indicated that high activities were present in lignifying cell walls. In mature needles, lignin was localized in walls of most needle tissues including mesophyll cells, and corresponded to 80 to 130 [mu]mol lignin monomers/g needle dry weight. Isoelectric focusing of apoplastic washing fluids and activity staining with guaiacol showed the presence of strongly alkaline peroxidases (isoelectric point [greater than or equal to] 9) in all developmental stages investigated. New isozymes with isoelectric points of 7.1 and 8.1 appeared during the major phase of lignification. These isozymes disappeared after lignification was terminated. A strong increase in peroxidase activity in autumn was associated with the appearance of acidic peroxidases (isoelectric point [less than or equal to] 3). These results suggest that soluble alkaline apoplastic peroxidases participate in lignin formation. Soluble acidic apoplastic peroxidases were apparently unrelated to developmentally regulated lignification in spruce needles.